The Begu Zulu vertical flute - Veenstra, A. J. F. (International Library of African Music, 1958)
In assessing the steps in the evolution in the construction of the vertical flute, the most important transition is from the flute with no whistle-head system, through the rudimentary whistle-head stage, to the whistle-head proper as manifest in the recorder and penny-whistle.
Keywords: South Africa; Ethnomusicology; Zulu (African people); Music; Flute; Flute music; Musical instruments; Africa; Instrument Construction; African Music; Flute (Instrument)